Nonlinear dependence in exchange rate returns: How do emerging Asian currencies compare with major currencies? - Wali, Muammer; Chan, Felix; Manzur, M. (Elsevier, 2017)
This paper provides a comparative review of the dynamic characteristics of monthly exchange rate changes for five major currencies relative to those of five emerging Asian economies over the last four decades. Using the British pound sterling as the numeraire currency, the data support nonlinear dependence in exchange rates for the less-liquid Asian currencies, while results for the major currencies are mixed. The more recent data indicate rejection of nonlinear dependence in major currencies.